CEO overconfidence and corporate policy - Kibria, Ishrar (2023)
The PhD thesis consists of three individual but related pieces of research. We extend the literature of CEO overconfidence influence in corporate strategies and provide latest findings on R&D investment, corporate governance structure and HR policy. This PhD thesis adopts empirical method of research, and the results are validated by several robustness checks.